EFFECTIVENESS OF PHOENIX DACTYLIFERA JUICE IN IMPROVING HEMOGLOBIN LEVELS: INSIGHTS FROM RECENT STUDIES - Abdullah, Dessy; Fharel Muhammad (Nusantara Hasana Journal, 2025)
Anemia is a prevalent health issue among adolescent girls due to increased iron requirements during growth and menstruation. The consumption of iron-rich foods, such as dates (Phoenix dactylifera), serves as a non-pharmacological alternative that effectively enhances hemoglobin levels. This article aims to review the effectiveness of date juice consumption in improving hemoglobin levels in adolescent girls with iron deficiency anemia. A systematic literature review was conducted by analyzing various studies from PubMed, Scopus, and Google Scholar databases between 2013 and 2023. The analyzed studies included experimental research, randomized controlled trials (RCTs), and meta-analyses related to date consumption and hemoglobin level improvement. Various studies indicate that regular consumption of date juice significantly increases hemoglobin levels. Experimental studies found that administering date juice for 14 days can enhance hemoglobin levels by up to 31.50%. Additionally, combining date consumption with iron supplementation has been proven more effective than iron supplementation alone, demonstrating a synergistic potential between natural foods and nutritional status. Based on this literature review, date juice consumption can serve as an effective dietary intervention to improve hemoglobin levels in adolescent girls with anemia. Further research is needed to understand the biological mechanisms underlying the benefits of dates in hemoglobin enhancement and to evaluate the long-term effects of this intervention in broader populations.